x+31−x2
3−x(1−x)2
3−x1+x2
3−x(1+x)2
3−x1−x2
Correct answer is E
11−x+21+x
= (1+x)+2(1−x)(1−x)(1+x)
= 1+x+2−2x1−x2
= 3−x1−x2
Solve: 6(x - 4) + 3(x + 7) = 3 ...
Simplify (6 - x - x2) ÷ (x2 - 4) ...
In the figure, PS = QS = RS and QSR - 100o, find QPR...
What angle represents grown up girls ? Correct to one decimal place ...
The shaded area represents ...
Let f(x) = 2x + 4 and g(x) = 6x + 7 here g(x) > 0. Solve the inequality f(x)g(x) < 1...
Solve the system of equation 2x + y = 32, 33y - x = 27...
Find the next three terms of the sequence; 0, 1, 1, 2, 3, 5, 8... ...